Stable isotope variations of daily precipitation from 2014–2018 in the central United States - Tian, Chao (Sci Data, 2019)
Stable isotopes of hydrogen and oxygen (δ(2)H, δ(18)O and δ(17)O) serve as powerful tracers in hydrological investigations. To our knowledge, daily precipitation isotope record especially (17)O-excess is rare in the mid-latitudes. To fill such knowledge gap, daily precipitation samples (n=446) were collected from June 2014 to May 2018 in Indianapolis, Indiana, U.S. A Triple Water Vapor Isotope Analyzer (T-WVIA) based on Off-Axis Integrated Cavity Output Spectroscopy (OA-ICOS) technique was used to concurrently measure precipitation isotopic variations (δ(2)H, δ(18)O and δ(17)O). Meanwhile, (17)O-excess and d-excess as second-order isotopic variables were calculated to provide additional information on precipitation formation and transport mechanisms. This study presents a four-year daily precipitation isotope dataset for mid-latitudes, and makes it available to researchers around the world who may use it as a reference for site comparisons and for assessing global hydrological models.